ENTREPREUNERSHIP TRAINING TO ENHANCE THE ENTERPRENEURIAL KNOWLEDGE AN SKILL OF THE DEAF COMMUNITY - Sari, Dewi Ratna; Rochmanti, Maftuchah; Rimbun, Rimbun (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Disabilities have equal rights as Indonesian citizens, including employment and entrepreneurship rights. The implementation of policies regarding the obligation of institutions to employ people with disabilities is still far from expected. Limited job information and access to education and job training programs are challenges in realizing economic independence for disabled persons. Therefore, it is very important to conduct community service activities aimed at increasing the entrepreneurial knowledge and skills of the Deaf Community through entrepreneurship training in order to reach economic independence. Nine Deaf Friends and four Sign Language Interpreters were involved in this study. The training was carried out by online method for three sessions, once a week. The questionnaires were distributed to assess the participants' level of knowledge before and after training. Each participant was required to develop and present a business plan in order to improve their entrepreneurial abilities. Two expert judges evaluated and provided constructive feedback to all participants.  The knowledge of participants before the training was 65.9 + 6.2, and increased by 12.4% to 74.1 + 10.8 after training. Participants were able to develop business proposals by the end of the program, with an average score of 7.6 + 0.7. Entrepreneurship training is able to enhance the entrepreneurial knowledge and skills of the Deaf Friends. This entrepreneurship training is a provision to assist the deaf community in creating and developing businesses that will lead to economic independence in the future.